WEB-BASED INSTRUCTIONAL ENVIRONMENTS: TOOLS AND TECHNIQUES FOR EFFECTIVE SECOND LANGUAGE ACQUISITION - Roman, Esperanza (International Journal of English Studies, 2002)
The potential of the Internet and especially the World Wide Web for the teaching and learning of foreign languages has grown spectacularly in the past five years. Nevertheless, designing and implementing sound materials for an online learning environment involves timeconsuming processes in which many instructors may be reluctant to participate. For this reason. Web-based course management systems (WCMSs) have begun to flourish in the market, in an effoi-t to assist teachers to create learning environments in which students have the necessary means to interact effectively with their peers, their instructors, and the course material.This article reviews the nature of WCMSs, their advantages and disadvantages, and their potential for language learning by focusing on key issues that surround the design implementation, and assessment of Web-based language courses, and by explaining how to integrate WCMSs to increase students' exposure to authentic materials and language-learning related activities, and to motivate them to engage in ineaningful communication processes and collaborative activities.